The Revitalization of Rimbo Larangan for the Minangkabau Tribe: an Innovation to Enhance Environmental Awareness among High School Students - Muhammad Aliman; Sumarmi Sumarmi; Ravinesh Rohit Prasad; Dahri Hi Halek; Rozana Eka Putri; Silvia Marni (Journal of Innovation in Educational and Cultural Research, 2025)
Minangkabau community of West Sumatra is familiar for its local wisdom called rimbo larangan, particularly on a concept dealing with environmental conservation. Excessive forest exploitation made the local wisdom of rimbo larangan needs to be revitalized by the community. The research aimed to determine 1) the local wisdom of the Minangkabau community in managing rimbo larangan and 2) the implementation of local wisdom rimbo larangan in geography learning. The research was conducted in the rimbo larangan in Nagari Alam Pauh Duo, South Solok Regency, and Koto Malintang Nagari, Agam Regency, West Sumatra Province. The research design was a qualitative descriptive, and data was collected through interview, observation, documentation dan literature review. The research results illustrated that rimbo larangan is in good condition though some differences in the management. The revitalization of rimbo larangan can be done by supplementing local wisdom topics to the geography syllabus in high school to develop students' environmental awareness.